Room-temperature-curing high-strength high-thermal-conductivity and high-electric-conductivity silver adhesive

By using a combination of end-hydroxy polydimethylsiloxane, carbon nanotubes and conductive particles in conductive silver glue, combined with ultrasonic dispersion and variable speed stirring technology, the existing conductive silver glue cannot take into account both high thermal conductivity and high bonding. The problem of force achieves efficient conductivity and stable bonding performance.

CN119490815APending Publication Date: 2025-02-21LINGGE NEW MATERIALS (SUZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411624765.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The conductive silver glue of existing silicone systems cannot take into account both high thermal conductivity and high adhesion.

Method used

A room temperature cured high-strength, high thermal conductivity silver glue, whose composition includes terminal hydroxyl polydimethylsiloxane, carbon nanotubes, conductive particles, silane coupling agent and crosslinking agent, through specific process steps such as ultrasonic dispersion Stir with variable speed to ensure that these components are evenly dispersed in the silver glue system.

Benefits of technology

It achieves high thermal conductivity and high adhesion, while reducing the use of silver powder, reducing the cost of raw materials, and improving the stability and scope of use of products.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a room-temperature-cured high-strength high-thermal-conductivity and high-electric-conductivity silver adhesive which is characterized by comprising the following components in parts by weight: 100 parts of hydroxyl-terminated polydimethylsiloxane, 2-6 parts of carbon nanotubes, 200-450 parts of conductive particles, 1-5 parts of a silane coupling agent, 5-12 parts of a cross-linking agent and 0.5-5 parts of a catalyst. The invention further discloses a preparation method of the room-temperature-curing high-strength high-thermal-conductivity and high-electric-conductivity silver adhesive. The room-temperature-cured high-strength high-thermal-conductivity and high-electrical-conductivity silver adhesive has the advantages of short curing time, low volume resistivity, high bonding strength and good electrical conductivity. The product is tested after being placed in an outdoor environment for 12 months for a long time, the volume resistivity and the bonding strength of the conductive silver adhesive disclosed by the invention are hardly influenced, and the conductive silver adhesive shows excellent weather resistance; the product has high stability and can be used for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor electronic materials, and specifically relates to a room temperature curing high-strength high-thermal conductivity conductive silver paste and a preparation method thereof. Background Art

[0002] In recent years, the semiconductor electronics industry has made great progress. Conductive adhesives are mainly composed of prepolymers and metal fillers. The mechanical properties and bonding properties of conductive adhesives are mainly determined by the polymer matrix; conductive fillers are mostly metal powders such as gold, silver, copper, nickel, etc. with low resistivity, which determine the electrical properties of conductive adhesives.

[0003] Among them, the matrix materials of conductive silver glue generally include acrylic acid, polyurethane, silicone, and epoxy resin. Among them, silicone has good heat resistance (above 260°C), electrical insulation, corrosion resistance and other advantages, and is a better material for making conductive silver glue. However, although the existing silicone conductive silver glue has a certain bonding force, it has a large gap in bonding force compared with the conductive silver glue of epoxy resin. In addition, the filler silver in the traditional silver conductive glue is polycrystalline micron silver powder particles, which rely on the mutual contact between the silver particles to form a conductive channel for conduction. However, due to the small contact area between the silver powder particles and the large number of nodes between the particles, the conductivity cannot be improved; and the use of silver micron sheets can increase the contact points to improve the conductivity and reduce the addition of silver powder, but the silver micron sheets have the problem of uneven dispersion and easy agglomeration during production and storage; therefore, most commercially available silver micron sheets will add fatty acids during the preparation process to prevent them from agglomerating, which makes the surface of these silver micron sheets often covered with a large amount of long-chain fatty acids. These long-chain fatty acids are not conductive, which reduces the electrical contact between the silver sheets. Fatty acids will also react with silver to form fatty acid silver, which further passivates the conductivity between the silver sheets. Moreover, the silver content in traditional conductive silver paste is very high, generally 70-80% by weight. When the silver powder doping amount is small, the conductive colloid cannot obtain a good conductive effect, and the cost of the conductive paste cannot be reduced, and its industrial application value is also subject to certain restrictions. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a room temperature curing high-strength thermal and electrical conductive silver paste and a preparation method thereof, aiming to solve the problem that the existing organic silicon system conductive silver paste cannot take into account both high thermal conductivity and high adhesion.

[0005] The objective of the present invention is achieved through the following technical solutions:

[0006] A room temperature curing high-strength high-thermal conductivity conductive silver glue comprises the following components by weight: 100 parts of terminal hydroxyl polydimethylsiloxane, 2-6 parts of carbon nanotubes, 200-450 parts of conductive particles, 1-5 parts of silane coupling agents, 5-12 parts of crosslinking agents, and 0.5-5 parts of catalysts.

[0007] Preferably, the terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane in a mass ratio of 1:(1-5), wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane is 300-600 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane is 1000-2000 mPa·s, and the viscosity of the terminal hydroxyl polydimethylsiloxane is 800-1500 mPa·s.

[0008] Preferably, the carbon nanotubes have a specific surface area of ​​100-200 m 2 / g of single-walled carbon nanotubes.

[0009] Preferably, the catalyst is dibutyltin dilaurate.

[0010] Preferably, the silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(β-aminoethyl)aminopropyltrimethoxysilane in a mass ratio of (1-3):1; the cross-linking agent is one of methyl tributylacetonato silane, vinyl butyl ketone oxime silane, methyl triacetonato silane or a mixture thereof.

[0011] Preferably, the conductive particles comprise a mixture of nano silver powder and flaky silver powder in a mass ratio of (3-5):(1-3); the particle size of the nano silver powder is 30nm to 60nm; and the particle size of the flaky silver powder is 3μm to 10μm.

[0012] Preferably, the method further comprises pre-treating the flaky silver powder, specifically, adding isopropyl alcohol to the flaky silver powder, heating to 60-80° C. while stirring and maintaining for 10-25 minutes for pre-treatment, removing the remaining isopropyl alcohol, and drying to remove the remaining isopropyl alcohol, thereby obtaining the pre-treated flaky silver powder.

[0013] A method for preparing the aforementioned room temperature curing high-strength high-thermal-conductivity conductive silver paste comprises the following steps:

[0014] 1) adding isopropanol to the flaky silver powder, heating to 60-80° C. for 10-25 minutes while stirring for pretreatment, removing the remaining isopropanol, and drying to remove the residual isopropanol, thereby obtaining pretreated micro-nano flaky silver powder;

[0015] 2) adding carbon nanotubes, part of the conductive particles and a silane coupling agent to the premixed hydroxy-terminated polydimethylsiloxane, and uniformly dispersing the mixture by ultrasonication to obtain a first mixed rubber material;

[0016] 3) adding the remaining conductive particles into the first mixed rubber material, and mixing them evenly by variable speed stirring to obtain a second mixed rubber material;

[0017] 4) Under vacuum conditions, a cross-linking agent and a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

[0018] In some specific embodiments, the process parameters of the ultrasonic dispersion in step 1) are to maintain the dispersion at a power of 70-200 W for 3-10 min.

[0019] In some specific embodiments, the variable speed stirring in step 2) is specifically: starting the stirring speed to 800-1500r / min, and stirring in a cycle of reducing the speed for 3s-increasing the speed for 3s-reducing the speed for 3s-increasing the speed for 3s; while stirring, continuously adjusting the position of the mechanical stirrer blades in the silver colloid system, and the stirring time is 5-15min.

[0020] An application of the aforementioned room temperature curing high-strength and high-thermal conductivity conductive silver paste in semiconductor chips.

[0021] Compared with the prior art, the present invention has at least the following advantages:

[0022] 1) The room temperature curing high-strength and high-thermal conductivity conductive silver paste of the present invention has flaky silver powder arranged in a flake structure, which is complete and continuous in the silver paste system, with a small total shrinkage, which is beneficial to improving the compactness of the silver paste after curing; however, the particle size of the flaky silver powder is relatively large, and the contact resistance between the flaky silver powder and the base glue is relatively poor. By adding nano silver powder, the gaps between the flaky silver powders can be filled, so that the adjacent flaky silver powders that were originally not in contact with each other can be contacted, thereby increasing the conductive path, or forming more parallel conductive paths in the silver paste, further reducing the addition of nano silver powder while improving the conductive performance of the entire system; that is, by using the compound use of nano silver powder and flaky silver powder, the entire system has a smaller volume resistivity while reducing the amount of silver powder added, thereby meeting the conductive performance requirements of existing chip bonding.

[0023] 2) The room temperature curing high-strength and high-thermal-conductivity conductive silver paste of the present invention effectively reduces the amount of long-chain fatty acids on the surface of the flaky silver powder by pre-treating the flaky silver powder; and then effectively improves the mechanical strength of the silver paste system by adding carbon nanotubes; and further reduces the long-chain fatty acids on the surface of the flaky silver powder while anchoring the flaky silver powder on the surface of the carbon nanotubes, thereby forming single-walled carbon nanotubes with flaky silver powder anchored on the surface. The carbon nanotubes can occupy a larger volume fraction in the silver paste system, and the volume resistivity of the conductive silver paste product can reach 10 -4 The Ω·cm level meets the conductive performance requirements of existing chip bonding; thus, when preparing the same level of conductive silver glue, the amount of silver powder added can be reduced, so that the price of conductive silver glue is reduced by 56-300%, effectively reducing the raw material cost of existing conductive silver glue; and the silver colloid with low silver content can also improve the product stability of the silver glue system, optimize the bonding strength and toughness of the silver glue, and greatly broaden the scope of use of the silver glue.

[0024] 3) The method for preparing the room temperature curing high-strength and high-thermal-conductivity conductive silver glue in the present application adopts a terminal hydroxyl polydimethylsiloxane of a specific viscosity, and uniformly pre-disperses the carbon nanotubes and part of the conductive particles by ultrasonic dispersion to obtain a first mixed glue material, and then adopts variable speed mechanical stirring (speed change + position change), combined with a specific system viscosity, so that the carbon nanotubes and the conductive particles are uniformly dispersed, and the sedimentation effect of the carbon nanotubes and the conductive particles caused by gravity is basically eliminated, so that the carbon nanotubes and the conductive particles in the magnesium melt are uniformly distributed in the silver glue system, which not only further improves the product stability of the silver glue, but also improves the thermal and electrical conductivity of the system while reducing the use of nano silver powder and reducing the production cost, and also provides technical support for increasing the volume fraction of carbon nanotubes and conductive particles in the base glue;

[0025] 4) The room temperature curing high-strength and high-thermal conductive silver paste provided by the present invention has short curing time, low volume resistivity, high bonding strength, and good conductive properties. The product of the present invention was placed in an outdoor environment for a long time for 12 months for testing. The volume resistivity and bonding strength of the conductive silver paste of the present invention were almost unaffected, showing excellent weather resistance; that is, the product of the present invention has high stability and can be used for a long time. DETAILED DESCRIPTION

[0026] The present invention will be further described in detail below in conjunction with specific embodiments. The following embodiments are merely illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.

[0027] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein include the endpoints of the range, and all integers and fractions within the range.

[0028] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0029] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.

[0030] The present invention provides a general and / or specific description of the materials and test methods used in the experiment. The test methods or test methods involved are all conventional methods unless otherwise specified; the reagents or instruments used are all conventional products available on the market, prepared or used in a conventional manner, unless the manufacturer is specified.

[0031] In the following embodiments, the terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane in a mass ratio of 1:1, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane is 500 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane is 2000 mPa·s, and the viscosity of the mixed terminal hydroxyl polydimethylsiloxane is 1250 mPa·s.

[0032] The carbon nanotubes have a specific surface area of ​​150 m 2 / g of single-walled carbon nanotubes.

[0033] The catalyst is dibutyltin dilaurate.

[0034] The silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(β-aminoethyl)aminopropyltrimethoxysilane in a mass ratio of 2:1; the crosslinking agent is methyl tributylidene oxime silane;

[0035] The conductive particles include a mixture of nano silver powder and flaky silver powder (pretreated flaky silver powder) in a mass ratio of 1:1; the particle size of the nano silver powder is 30nm to 60nm; the particle size of the flaky silver powder (pretreated flaky silver powder) is 3μm to 10μm.

[0036] Example 1

[0037] This embodiment provides a method for preparing a room temperature curing high-strength high-thermal-conductivity conductive silver paste, comprising the following steps:

[0038] 1) adding isopropyl alcohol to the flaky silver powder (the ratio of the mass of the flaky silver powder to the volume of the isopropyl alcohol is 1:10), heating to 80° C. for 15 minutes while stirring for pretreatment, removing the remaining isopropyl alcohol, and drying to remove the residual isopropyl alcohol, thereby obtaining pretreated micro-nano flaky silver powder;

[0039] 2) premixing 2 parts of carbon nanotubes, 150 parts of conductive particles, 3 parts of silane coupling agent and 100 parts of hydroxy-terminated polydimethylsiloxane, and ultrasonically dispersing them at a power of 80 W for 10 minutes to obtain a first mixed rubber material;

[0040] 3) adding the remaining 50 parts of conductive particles to the first mixed rubber material, starting stirring and increasing the speed to 900 r / min, and stirring in a cycle of reducing the speed for 3s-increasing the speed for 3s-reducing the speed for 3s-increasing the speed for 3s; while stirring, constantly adjusting the position of the mechanical stirrer blade in the silver glue system, the stirring time is 15 minutes, and a second mixed rubber material is obtained;

[0041] 4) After vacuum cooling, 7 parts of a cross-linking agent and 1.5 parts of a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

[0042] Example 2

[0043] This embodiment provides a method for preparing a room temperature curing high-strength high-thermal-conductivity conductive silver paste, comprising the following steps:

[0044] 1) adding isopropyl alcohol to the flaky silver powder (the ratio of the mass of the flaky silver powder to the volume of the isopropyl alcohol is 1:10), heating to 80° C. for 15 minutes while stirring for pretreatment, removing the remaining isopropyl alcohol, and drying to remove the residual isopropyl alcohol, thereby obtaining pretreated micro-nano flaky silver powder;

[0045] 2) pre-mixing 3.5 parts of carbon nanotubes, 180 parts of conductive particles, 3 parts of silane coupling agent and 100 parts of hydroxy-terminated polydimethylsiloxane, and ultrasonically dispersing them at a power of 120 W for 8 minutes to obtain a first mixed rubber material;

[0046] 3) adding the remaining 120 parts of conductive particles to the first mixed rubber material, starting stirring and increasing the speed to 1000 r / min, and stirring in a cycle of reducing the speed for 3s-increasing the speed for 3s-reducing the speed for 3s-increasing the speed for 3s; while stirring, constantly adjusting the position of the mechanical stirrer blade in the silver glue system, the stirring time is 10 minutes, and a second mixed rubber material is obtained;

[0047] 4) After vacuum cooling, 8 parts of a cross-linking agent and 2 parts of a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

[0048] Example 3

[0049] This embodiment provides a method for preparing a room temperature curing high-strength high-thermal-conductivity conductive silver paste, comprising the following steps:

[0050] 1) adding isopropyl alcohol to the flaky silver powder (the ratio of the mass of the flaky silver powder to the volume of the isopropyl alcohol is 1:10), heating to 80° C. for 15 minutes while stirring for pretreatment, removing the remaining isopropyl alcohol, and drying to remove the residual isopropyl alcohol, thereby obtaining pretreated micro-nano flaky silver powder;

[0051] 2) pre-mixing 5 parts of carbon nanotubes, 200 parts of conductive particles, 3 parts of silane coupling agent and 100 parts of hydroxy-terminated polydimethylsiloxane, and ultrasonically dispersing them at a power of 150 W for 5 minutes to obtain a first mixed rubber material;

[0052] 3) adding the remaining 180 parts of conductive particles to the first mixed rubber material, starting stirring and increasing the speed to 1200 r / min, and stirring in a cycle of reducing the speed for 3s-increasing the speed for 3s-reducing the speed for 3s-increasing the speed for 3s; while stirring, constantly adjusting the position of the mechanical stirrer blade in the silver glue system, the stirring time is 5 minutes, and a second mixed rubber material is obtained;

[0053] 4) After vacuum cooling, 8 parts of a cross-linking agent and 2 parts of a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

[0054] Example 4

[0055] This embodiment provides a method for preparing a room temperature curing high-strength and high-thermal conductivity conductive silver paste, the components and proportions of which are basically the same as those of Example 2, except that the weight fraction of the conductive particles is 450 parts (step 2) and the amount added in step) is 250 parts + 200 parts respectively), and the steps and process parameters are the same as those of Example 2.

[0056] Comparative Example 1

[0057] This comparative example provides a method for preparing a room temperature curing high-strength and high-thermal conductivity conductive silver paste, the components and proportions of which are basically the same as those of Example 4, except that only unpretreated micron-sized flaky silver powder is added (i.e., no carbon nanotubes are added and the surface of the micron-sized flaky silver powder is not pretreated); the steps and process parameters are the same as those of Example 4.

[0058] Comparative Example 2

[0059] This comparative example provides a method for preparing a room temperature curing high-strength and high-thermal conductivity conductive silver paste, the components and proportions of which are basically the same as those of Example 4, except that only pretreated micron-sized flaky silver powder is added, and no carbon nanotubes are added; the steps and process parameters are the same as those of Example 4.

[0060] Comparative Example 3

[0061] This comparative example provides a method for preparing a room temperature curing high-strength and high-thermal conductivity conductive silver paste, the components and proportions of which are basically the same as those of Example 4, except that only carbon nanotubes are added and the micron-sized flaky silver powder is not pretreated; the steps and process parameters are the same as those of Example 4.

[0062] Comparative Example 4

[0063] This comparative example provides a method for preparing a room temperature curing high-strength high-thermal-conductivity conductive silver paste, the components and proportions of which are basically the same as those of Example 4, except that the viscosity of the mixed terminal hydroxyl polydimethylsiloxane added is different, specifically: wherein the terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane in a mass ratio of 1:3, wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane is 500mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane is 2000mPa·s, and the viscosity of the mixed terminal hydroxyl polydimethylsiloxane is 1650mPa·s. The steps and process parameters are the same as those of Example 4.

[0064] Comparative Example 5

[0065] This comparative example provides a method for preparing a room temperature curing high-strength high-thermal-conductivity conductive silver paste, the components and proportions of which are the same as those of Example 4; the steps and process parameters are basically the same as those of Example 4, except that variable speed stirring is not used, but constant speed stirring is used, specifically:

[0066] 1) adding isopropyl alcohol to the flaky silver powder (the ratio of the mass of the flaky silver powder to the volume of the isopropyl alcohol is 1:10), heating to 80° C. for 15 minutes while stirring for pretreatment, removing the remaining isopropyl alcohol, and drying to remove the residual isopropyl alcohol, thereby obtaining pretreated micro-nano flaky silver powder;

[0067] 2) premixing 3.5 parts of carbon nanotubes, 250 parts of conductive particles, 3 parts of silane coupling agent and 100 parts of hydroxy-terminated polydimethylsiloxane, and ultrasonically dispersing them at a power of 120 W for 8 minutes to obtain a first mixed rubber material;

[0068] 3) adding the remaining 200 parts of conductive particles to the first mixed rubber material, and stirring evenly at a speed of 1000 r / min; while stirring, constantly adjusting the position of the mechanical stirrer blade in the silver glue system, and stirring for 10 minutes to obtain a second mixed rubber material;

[0069] 4) After vacuum cooling, 8 parts of a cross-linking agent and 2 parts of a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

[0070] Comparative Example 6

[0071] This comparative example provides a method for preparing a room temperature curing high-strength high-thermal-conductivity conductive silver paste, the components and proportions of which are the same as those of Example 4; the steps and process parameters are basically the same as those of Example 4, except that the position of the mechanical stirring blade in the silver paste system is not changed, specifically:

[0072] 1) adding isopropyl alcohol to the flaky silver powder (the ratio of the mass of the flaky silver powder to the volume of the isopropyl alcohol is 1:10), heating to 80° C. for 15 minutes while stirring for pretreatment, removing the remaining isopropyl alcohol, and drying to remove the residual isopropyl alcohol, thereby obtaining pretreated micro-nano flaky silver powder;

[0073] 2) pre-mixing 5 parts of carbon nanotubes, 250 parts of conductive particles, 3 parts of silane coupling agent and 100 parts of hydroxy-terminated polydimethylsiloxane, and ultrasonically dispersing them at a power of 120 W for 8 minutes to obtain a first mixed rubber material;

[0074] 3) adding the remaining 200 parts of conductive particles to the first mixed rubber material, starting stirring and increasing the speed to 1000 r / min, and simultaneously carrying out a cycle of stirring for 10 min in the manner of reducing the speed for 3 s-increasing the speed for 3 s-reducing the speed for 3 s-increasing the speed for 3 s, during the stirring process, the blade of the mechanical stirrer is in the middle position of the silver glue system, to obtain a second mixed rubber material;

[0075] 4) After vacuum cooling, 8 parts of a cross-linking agent and 2 parts of a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

[0076] Performance Testing:

[0077] 1. Test Method

[0078] 1) Bonding strength test: The bonding strength test specimen uses conductive silver glue as the adhesive and aluminum sheet as the substrate. The sample adopts a single-sided overlap test piece. The bonding strength test is carried out on a microcomputer-controlled electronic universal testing machine.

[0079] 2) Curing time: The time it takes for the volume resistivity and bonding strength of the conductive silver paste to reach stability.

[0080] 3) Weather resistance test: Place in outdoor environment and monitor its volume resistivity and bonding strength for a fixed period of time.

[0081] 2. This application takes Examples 1-4 and Comparative Examples 1-6 as examples to test the performance of the prepared silver paste, wherein the thermal conductivity (W / m˙k) is tested according to the standard ASTM-D5470, the adhesive force (Mpa) is tested according to the standard GB / T7124-2008, the room temperature storage period (days) is tested according to GB / T7123.2-2002, and the resistivity (Ω˙cm) is tested according to GB / T1410-2006. The specific test results are as follows:

[0082] As shown in Table 1:

[0083] Thermal conductivity (W / m˙k) Adhesion strength(Mpa) Room temperature storage period (days) Resistivity(Ω˙cm) Example 1 27 4.8 365 days <![CDATA[3.8×10 -4 ]]> Example 2 36 4.5 365 days <![CDATA[8.7×10 -4 ]]> Example 3 43 4.2 365 days <![CDATA[4.2×10 -5 ]]> Example 4 52 4.0 365 days <![CDATA[1.3×10 -5 ]]> Comparative Example 1 20 1.3 365 days <![CDATA[2.4×10 -3 ]]> Comparative Example 2 30 1.5 365 days <![CDATA[1.2×10 -4 ]]> Comparative Example 3 25 3.5 365 days <![CDATA[7.6×10 -3 ]]> Comparative Example 4 38 3.7 365 days <![CDATA[4.2×10 -4 ]]> Comparative Example 5 32 3.2 243 days <![CDATA[3.1×10 -4 ]]> Comparative Example 6 35 3.3 243 days <![CDATA[3.5×10 -4 ]]>

[0084] It can be seen from the table that the room temperature curing high strength high thermal conductivity conductive silver paste provided by the present application has excellent thermal conductivity, electrical conductivity, adhesion and storage stability;

[0085] By comparing Examples 1-4, it can be seen that the electrical conductivity and thermal conductivity of the silver paste in the present application increase with the increase in the proportion of conductive particles, while the bonding performance decreases with the decrease in the proportion of conductive particles. The bonding performance of the silver paste in the present application is not less than 4.0Mpa.

[0086] By comparing Example 4 with Comparative Examples 1, 2 and 3, it can be seen that in the present application, by adding micron-sized flaky silver powder and single-walled carbon nanotubes, the electrical conductivity and thermal conductivity of the room temperature curing high-strength thermal conductive silver paste can be effectively improved. The addition of carbon nanotubes can not only assist the excellent mechanical strength of the base glue system, but also effectively improve the thermal conductivity, electrical conductivity and bonding strength of the base glue system. It can be seen from the data that the use of single-walled carbon nanotubes and pretreated micron-sized flaky silver powder can synergistically improve the thermal conductivity and electrical conductivity of the room temperature curing high-strength high-thermal conductive silver paste, and can also assist the excellent bonding performance of the silver paste system;

[0087] By comparing Example 4 with Comparative Examples 4-6, it can be seen that by comparing Example 2 with Comparative Example 4, the viscosity of the mixed hydroxyl-terminated polydimethylsiloxane is changed. In the preparation process step of the present application, the viscosity of the mixed hydroxyl-terminated polydimethylsiloxane is increased. Although it can prevent the sedimentation of the conductive particles with high density during the preparation and storage process, the high viscosity causes the conductive particles to be unevenly dispersed in the system, thereby reducing the conductive and thermal conductivity.

[0088] By comparing Example 4 with Comparative Examples 5 and 6, it can be seen that the conductive particles cannot be evenly dispersed in the entire silver paste system by using a constant speed or a constant position. This is mainly manifested in that the density of the conductive particles is large, and sedimentation is easy to occur during the production and storage process, resulting in uneven dispersion, which in turn affects the conductive and thermal conductive properties of the silver paste.

[0089] In summary, the room temperature curing high-strength and high-thermal conductivity conductive silver paste provided in the present application, by adopting a mixed end-hydroxyl polydimethylsiloxane of a specific viscosity and combining ultrasonic stirring and variable speed stirring (variable speed, variable position), effectively improves the dispersibility of conductive particles and carbon nanotubes in the silver paste system, while also basically eliminating the sedimentation problem of conductive particles due to their density being greater than the base glue, so that the conductive particles can be evenly distributed in the base glue system.

[0090] In summary, the room temperature curing high-strength and high-thermal conductivity conductive silver paste provided in the present application adopts single-walled carbon nanotubes and performs surface pretreatment on micron-sized flaky silver powder; then adopts a base glue of specific viscosity (mixed end-hydroxyl polydimethylsiloxane), and combines specific process steps (using ultrasonic premixing and variable speed stirring) to prepare a silver paste with high thermal conductivity and electrical conductivity, excellent bonding performance and stability; at the same time, the conductive particles in the silver paste system are far lower than those in the preparation of silver paste with the same volume resistivity, which reduces the use of conductive particles and reduces production costs, making it suitable for popularization and application.

[0091] This application also takes Example 4 as an example to test the mechanical strength of the prepared room temperature curing high-strength high-thermal-conductivity conductive silver paste, and the results are shown in Table 2:

[0092] Tensile Strength Elongation at break Tear Strength Example 4 3.8MpA 380% 12.7kN / m

[0093] As can be seen from Table 2, the room temperature curing high-strength and high-thermal conductive silver paste provided in the present application also has excellent mechanical strength and can be used in scenarios requiring high strength.

[0094] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A room temperature curing high strength high thermal conductivity conductive silver paste, characterized in that: The composition comprises the following components in parts by weight: 100 parts of terminal hydroxyl polydimethylsiloxane, 2-6 parts of carbon nanotubes, 200-450 parts of conductive particles, 1-5 parts of silane coupling agent, 5-12 parts of crosslinking agent and 0.5-5 parts of catalyst.

2. The room temperature curing high-strength high-thermal-conductivity conductive silver paste according to claim 1, characterized in that: The terminal hydroxyl polydimethylsiloxane comprises a low-viscosity terminal hydroxyl polydimethylsiloxane and a high-viscosity terminal hydroxyl polydimethylsiloxane in a mass ratio of 1:(1-5), wherein the viscosity of the low-viscosity terminal hydroxyl polydimethylsiloxane is 300-600 mPa·s, the viscosity of the high-viscosity terminal hydroxyl polydimethylsiloxane is 1000-2000 mPa·s, and the viscosity of the terminal hydroxyl polydimethylsiloxane is 800-1500 mPa·s.

3. The room temperature curing high strength high thermal conductivity conductive silver paste according to claim 1, characterized in that: The carbon nanotubes have a specific surface area of ​​100-200 m 2 / g of single-walled carbon nanotubes.

4. The room temperature curing high strength high thermal conductivity conductive silver paste according to claim 1, characterized in that: The catalyst is dibutyltin dilaurate.

5. The room temperature curing high strength high thermal conductivity conductive silver paste according to claim 4, characterized in that: The silane coupling agent is a mixture of γ-(2,3-epoxypropoxy)propyltrimethoxysilane and γ-(β-aminoethyl)aminopropyltrimethoxysilane in a mass ratio of (1-3):1; the crosslinking agent is one of methyl tributylacetonato silane, vinyl butyl ketone oxime silane, methyl triacetonato silane or a mixture thereof.

6. The room temperature curing high strength high thermal conductivity conductive silver paste according to claim 1, characterized in that: The conductive particles include a mixture of nano silver powder and flaky silver powder in a mass ratio of (3-5):(1-3); wherein the particle size of the nano silver powder is 30nm to 60nm; and the particle size of the flaky silver powder is 3μm to 10μm.

7. The room temperature curing high strength high thermal conductivity conductive silver paste according to claim 1, characterized in that: The method further includes pre-treating the flaky silver powder, specifically, adding isopropyl alcohol to the flaky silver powder, heating to 60-80° C. while stirring and maintaining for 10-25 minutes for pre-treatment, removing the remaining isopropyl alcohol, and drying to remove the remaining isopropyl alcohol, thereby obtaining the pre-treated flaky silver powder.

8. A method for preparing a room temperature curable high-strength high-thermal-conductivity conductive silver paste according to any one of claims 1 to 7, characterized in that: The steps include: 1) adding isopropanol to the flaky silver powder, heating to 60-80° C. for 10-25 minutes while stirring for pretreatment, removing the remaining isopropanol, and drying to remove the residual isopropanol, thereby obtaining pretreated micro-nano flaky silver powder; 2) adding carbon nanotubes, part of the conductive particles and a silane coupling agent to the premixed hydroxy-terminated polydimethylsiloxane, and uniformly dispersing the mixture by ultrasonication to obtain a first mixed rubber material; 3) adding the remaining conductive particles into the first mixed rubber material, and mixing them uniformly by variable speed stirring to obtain a second mixed rubber material; 4) Under vacuum conditions, a cross-linking agent and a catalyst are added to the second mixed adhesive, vacuum stirred to defoam, and sealed and packaged to obtain the room temperature curing high-strength and high-thermal conductivity conductive silver adhesive.

9. The method for preparing the room temperature curing high tensile conductive and thermal conductive silver paste according to claim 8, characterized in that: The process parameters of the ultrasonic dispersion in step 1) are: maintaining 3-10 minutes at a power of 70-200 W; the variable speed stirring in step 2) is specifically: starting the stirring speed to 800-1500 r / min, and at the same time, stirring in a cycle of reducing the speed for 3s-increasing the speed for 3s-reducing the speed for 3s-increasing the speed for 3s; while stirring, continuously adjusting the position of the mechanical stirrer blade in the silver colloid system, and the stirring time is 5-15 minutes.

10. Use of the room temperature curing high-strength high-thermal-conductivity conductive silver paste as claimed in any one of claims 1 to 7 in a semiconductor chip.

Citation Information

Cited By

  • High-durability organic silicon conductive adhesive and preparation method thereof

    CN119955467A

  • An epoxy conductive silver paste for electronic-grade packaging and its preparation method

    CN122668672A